Valence politics and voting in the 2012 U.S. presidential election. (December 2015) - Clarke, Harold; Reifler, Jason; Scotto, Thomas J.; Stewart, Marianne C.; Whiteley, Paul
Abstract: This paper analyzes voting behavior in the 2012 U.S. presidential election. Using national survey data gathered in the 2012 Political Support in America project, the paper investigates the ability of a valence politics model of electoral choice to account for voting in that election. Multivariate analyses reveal that a valence politics model comprised of judgments about party performance on important issues, flexible partisan attachments, and images of the two major presidential candidates outperforms rival models and provides a parsimonious and powerful explanation of decisions voters made. The analyses show that although several factors had significant effects on the vote, the impact of candidate images was especially strong. Although many voters expressed doubts about Obama's competence, even more were unconvinced that Romney offered a viable alternative. Most voters were unenthusiastic about Romney and this cost him dearly at the ballot box. Highlights: Romney's image very negative. Obama vulnerable; performance ratings were weak. Upward Republican partisan dynamics started after GOP convention. Racial attitudes had significant effects on vote. Republicans did not capitalize on economy or other valence issues.